Typologies of policymakers’ perception toward energy transition in Korea: philosophy and resources - 이유현; 조민혁; 박형준 (International Review of Public Administration, 2022)
Energy transition is a crucial process in fighting climate change. Most policymakers agree with its importance, however, they follow different approaches toward achieving energy transition. This study examines policymakers’ perceptions of dominant energy resources and their philosophy toward energy transition. The study employed the Q analysis, which is suitable for exploring policymakers’ perceptions. A total of four major environmental philosophies were identified, namely ecocentrism, technocentrism, preventism, andmarketism. The analysis of the results concluded that four types of perceptions could be derived fromthe factor analysis. The most popular type of perception is based on the comprehensive attitude that combines environmental values, safety, and economy. Through the analysis, two crucial implications are suggested: the necessity of energy mix and the long-term feasibility of energy transition. The results of our analysis can serve as useful evidence for establishing a robust energy transition policy.
Keywords: Energy transition; Korean energy policy; policymaker; Q methodology